ESG PERFORMANCE AND CORPORATE TRANSPARENCY: A SYSTEMATIC LITERATURE REVIEW - Mulkan Teguh Sutrisno; Abdul Malik; Mis Widya Andelina (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to systematically identify and analyze the relationship between Environmental, Social, and Governance (ESG) performance and corporate transparency. The review employs a Systematic Literature Review (SLR) approach using the PRISMA method, based on ten international scholarly articles published between 2018 and 2025. The synthesis results indicate that ESG performance positively contributes to enhancing the quality of information disclosure, corporate reputation, and investor trust. However, challenges such as greenwashing practices, regulatory gaps, and organizational capacity constraints hinder the effective implementation of ESG transparency. The study concludes that ESG should not only be viewed as a compliance tool but also as a communication and risk management strategy that directly affects corporate value. Recommendations are provided for business actors, policymakers, and academics to strengthen ESG reporting systems in the future